The Rise of Populist Nationalism and the Renegotiation of NAFTA. (16th March 2018) - Lester, Simon; Manak, Inu
Abstract: Countries that have traditionally led the way in promoting economic globalization and its institutions have seen a recent surge of populism and nationalism, calling into question the liberal international economic order. The rhetoric of these critics is often vague, however, and it is unclear what a populist or nationalist approach to international economic policy would look like. The North American Free Trade Agreement (NAFTA) renegotiation initiated by the Trump administration could give us the first clues. Will their proposals destroy the trading system as we know it, or merely tweak it? This article examines these issues by discussing the concepts of nationalism and sovereignty, and then viewing the Trump administration's specific NAFTA proposals through those lenses.